Speech, Structure, and Behavior on the Supreme Court of India - Chandrachud, Abhinav (Columbia Journal of Asian Law, 2012)
This Article captures what can be termed as “structural” and “behavioral” features of the Indian Supreme Court’s decision-making process in speech cases. It demonstrates that speech cases are not a high priority on the docket of the Supreme Court of India, which is worrying in a liberal democracy. The Chief Justice of India participates less in these cases than he once had, and assigns these cases to smaller panels. Speech cases generate less debate and deliberation than before and engender fewer dissents and concurring opinions. The proportion of speech cases relative to the size of the court’s docket is also troublingly small. If sixty years of decision-making in speech cases on the Supreme Court of India were viewed as a seamless narrative, one could conclude that the Court has been ambivalent towards speech harboring neither a clear bias in favor of nor against speech.